Description of three new species of Ampelisca (Crustacea: Amphipoda: Ampeliscidae) from Southwestern Atlantic, with a key of the genus for Brazilian species - Valério-Berardo, Maria Teresa (Zootaxa, 2007)
Ampelisca species are inhabitant of soft bottom marine benthic communities of tropical to cold – temperate zones. Prior to this paper, 11 species of the genus were recognized from Brazilian coast. Three new species of Ampelisca are herein described: Ampelisca longipropoda, Ampelisca meridionalis and Ampelisca youngi. The specimens were dredged from the continental shelf of Southwestern Atlantic Ocean between the latitudes 22°06’S and 34°32’S. A key to the Ampelisca species of the Brazilian coast is provided.